The effect of fluconazole on ritonavir and saquinavir pharmacokinetics in HIV-1-infected individuals - Koks, C H W (Blackwell Science Inc, 2001)
AIMS: To study the effect of fluconazole on the steady-state pharmacokinetics of the protease inhibitors ritonavir and saquinavir in HIV-1-infected patients. METHODS: Five subjects treated with saquinavir and three with ritonavir received the protease inhibitor alone (saquinavir 1200 mg three times daily, ritonavir 600 mg twice daily) on day 1, and the same protease inhibitor in combination with fluconazole (400 mg on day 2 and 200 mg on days 3 to 8). Pharmacokinetic parameters were determined on days 1 and 8. RESULTS: In the saquinavir group, the median increase in the area under the plasma concentration vs time curve was 50% from 1800 µg l(−1) h to 2700 µg l(−1) h (P = 0.04, median increase: 900 µg l(−1) h; 2.5 and 97.5 percentile: 500–1300), and 56% for the peak concentration in plasma (from 550 to 870 µg l(−1), P = 0.04; median increase: 320 µg l(−1) h, 2.5 and 97.5 percentile: 60–450 µg l(−1)). In the ritonavir group, there were no detectable changes in the pharmacokinetic parameters on addition of fluconazole. CONCLUSIONS: Because of the favourable safety profile of saquinavir, dose adjustments are probably not necessary with concomitant use of fluconazole, as is the case for ritonavir.